(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article provides comments on the introduction of mystical ideas into Uzbek literature and the development of Sufi literature. The gradual development of mystical ideas in Uzbek literature and its study, including the literary and critical views of Najmiddin Kamilov and Ibrohim Hakqul, are analyzed. In addition, the influence of Sufi ideas in the works of such creators as Rabguziy, Yassaviy, Navoiy, Mashrab and the new interpretation of the Sufi tradition in contemporary literature are discussed.